Le rôle de Francesco Guicciardini dans le Tumulto del venerdì (26 avril 1527) selon certaines sources non florentines - Marcello Simonetta (Laboratoire Italien, 2016)
In his History of Italy (XVIII, 7), Francesco Guicciardini celebrated his own role as saviour of the patria, i.e. of Florence, during the so-called Tumulto del venerdì, the failed anti-Medici coup of 26 April 1527. The forgotten testimony by the Urbino ambassador Orazio Floridi scales down the version of facts provided by Guicciardini, raising the question of the relationship between autobiography and historiography. This essay explores the double role of Guicciardini as papal Luogotenente and as Florentine citizen who was about to make the decision of aiding Florence while leaving open the way to the devastation of Rome. In his Accusatoria Guicciardini drew up charges against himself that, in the light of this contribution and of historical hindsight, seem more than grounded. In his Accusatoria Guicciardini drew up charges against himself that, in the light of this contribution, seem more than grounded.